Prognostic Significance of Fibrosis, Blast Ratio and Biomarkers in Adult Acute Lymphoblastic Leukemia Patients - Eray Arslan; Engin Kelkitli (Izmir Katip Celebi University Faculty of Medicine, 2026)
Aim: Despite high remission rates achieved with induction therapy in adult acute lymphoblastic leukemia (ALL), long-term survival outcomes remain unsatisfactory. This study aimed to explore the prognostic value of bone marrow fibrosis, bone marrow blast percentage, and selected serum biomarkers—albumin, beta-2 microglobulin (B2M), and lactate dehydrogenase (LDH)—at diagnosis in adult ALL patients. Materials and Methods: We retrospectively evaluated 116 adults diagnosed and treated for ALL between January 2006 and December 2018 in a single tertiary hematology center. Demographic, clinical, laboratory, genetic, and pathological characteristics were reviewed. The degree of bone marrow fibrosis was scored from 0 to 4. Survival outcomes were analyzed using Kaplan–Meier and Cox regression models. Results: The mean patient age was 43.1 years. Complete remission following induction was achieved in 83.6% of cases, and 40 patients underwent allogeneic stem cell transplantation. The median overall survival was 41.4 months, with an overall survival rate of 52.6%. No significant prognostic correlation was observed for serum LDH, B2M, albumin levels, or blast percentage at diagnosis. Conversely, advanced bone marrow fibrosis (grade 2–4) was significantly linked with inferior survival (p=0.024). Conclusion: Bone marrow fibrosis at presentation may serve as an independent predictor of poor prognosis in adult ALL, while the evaluated biomarkers and blast percentage were not prognostically informative. Integrating fibrosis assessment into clinical risk models could improve individualized treatment strategies and long-term outcomes.